2021
DOI: 10.1021/acs.biomac.1c01268
|View full text |Cite
|
Sign up to set email alerts
|

Double-Modified Bacterial Cellulose/Soy Protein Isolate Composites by Laser Hole Forming and Selective Oxidation Used for Urethral Repair

Abstract: In this study, a double-modified bacterial cellulose/ soybean protein isolate (DMBC/SPI), a new type of urethral tissue engineering scaffold with good biocompatibility, biodegradability, and cell-oriented growth, was prepared. Bacterial cellulose (BC) was physically and chemically modified by laser hole forming and selective oxidation to obtain the double-modified bacterial cellulose (DMBC). The soybean protein isolate (SPI) was compounded on DMBC to obtain DMBC/SPI with better biocompatibility. DMBC/SPI was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…129 Animal test studies showed that the DMBC/SPI promoted the healing of the damaged urethra with no inflammatory reactions; moreover, the repaired urethra was smooth and continuous. 129 In another vein, a cheap fabrication technique using allbiobased materials such as nanohydroxyapatite (n-HAP), oxidized bacterial cellulose (OBC), and chitosan for bone repair, is reported. 130 The n-HAP was prepared employing in situ crystallization of Ca 2+ /PO 4 2− solution and subsequently distributed evenly into the OBC and CS mixture, poured into a mold for freeze-drying, after which CS/OBC/n-HAP scaffolds were constructed.…”
Section: Biomedical and Tissue Engineeringmentioning
confidence: 99%
See 3 more Smart Citations
“…129 Animal test studies showed that the DMBC/SPI promoted the healing of the damaged urethra with no inflammatory reactions; moreover, the repaired urethra was smooth and continuous. 129 In another vein, a cheap fabrication technique using allbiobased materials such as nanohydroxyapatite (n-HAP), oxidized bacterial cellulose (OBC), and chitosan for bone repair, is reported. 130 The n-HAP was prepared employing in situ crystallization of Ca 2+ /PO 4 2− solution and subsequently distributed evenly into the OBC and CS mixture, poured into a mold for freeze-drying, after which CS/OBC/n-HAP scaffolds were constructed.…”
Section: Biomedical and Tissue Engineeringmentioning
confidence: 99%
“…128 A doublemodified bacterial cellulose/soybean protein isolate (DMBC/ SPI), was used to create a new type of urethral tissue scaffold that possesses optimal biocompatibility, biodegradability (with notable degradation rate), ease of suturing, and cell-oriented growth, to mitigate the problems (for example, stenosis recurrence, fistula formation, and foreign body reactions) associated with currently employed acellular matrix and degradable polymers (for example, polycaprolactone and polylactic acid) in urethral tissue engineering. 129 Animal test studies showed that the DMBC/SPI promoted the healing of the damaged urethra with no inflammatory reactions; moreover, the repaired urethra was smooth and continuous. 129 In another vein, a cheap fabrication technique using allbiobased materials such as nanohydroxyapatite (n-HAP), oxidized bacterial cellulose (OBC), and chitosan for bone repair, is reported.…”
Section: Biomedical and Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Jun Lin et al constructed a defect-rich Ti-based MOF with a greatly improved sonosensitizing effect, which can facilitate the US-triggered electron–hole separation . However, the charge of the organic ligand transfers to the metal ions/clusters via ligand-to-metal charge transfer, which cannot induce effective charge separation and thus cause rapid exciton quenching, resulting in the impairment of the SDT effect. The charge transfer via the metal-to-metal charge transfer without this drawback can efficiently improve the catalytic reaction. Therefore, the construction of an MOF heterostructure by introducing heterogeneous metal atoms onto the surface of an MOF is an alternative strategy to augment the SDT effect.…”
Section: Introductionmentioning
confidence: 99%